Renewal of Implementing Regulations in Minimizing Control in Limited Liability Companies Outside of Acquisitions - Pakpahan, Kartina; Tanjaya, Willy; Ferina, Wulan Me (Batulis Civil Law Review, 2024)
Introduction: The problem is that the definition of "control" of a company is not found explicitly in the Company Law, resulting in the emergence of practices of "control" of companies which are carried out not in accordance with the provisions as stipulated in the provisions of Article 1 point 11 and Article 125 paragraph (3) of the Company Law. When taking over company shares, it does not always result in a change in control of the company if the number of shares taken over does not exceed 50% of the company's shares. If the takeover of shares exceeds 50% of the company's shares, the party taking over a company will become the controller of the party being taken over.Purposes of the Research:  The control intended by UUPT is very limited and cannot be interpreted more broadly. Methods of the Research: The research method used in this research is Empirical Legal Research, which uses a sociological legal approach focusing on reality by examining the application of law, in this case the PT UU, which is used as a basis for the formation and implementation of a Legal Entity (limited liability company).Results of the Research: The results of the research found the first fact that there were actions to control limited liability companies that were not in accordance with the provisions of Article 1 number 11 and Article 125 paragraph (3) of the Company Law and the aims and objectives of the Articles of Association of the Deed of Establishment were not achieved. These findings occurred at PT. ESG. Second, there is the involvement of a Notary in legalizing the actions of the Commissioner of PT. ESG to control PT. ESG Beyond Acquisitions. Third, there is a conflict between the norms of Article 102 paragraph 1 of the Company Law with Article 102 paragraph 4 of the Company Law regarding the "Requirement to seek approval from the GMS" to transfer assets, but the entire assets of PT. ESG has been transferred without asking for approval from the GMS and a Deed of Sale and Purchase Agreement and Transfer of Rights has been issued by a Notary.